2018
DOI: 10.1103/physrevd.98.124027
|View full text |Cite
|
Sign up to set email alerts
|

Strong lensing constraints on modified gravity models

Abstract: We impose the first strong-lensing constraints on a wide class of modified gravity models where an extra field that modifies gravity also couples to photons (either directly or indirectly through a coupling with baryons) and thus modifies lensing. We use the nonsingular isothermal ellipsoid (NIE) profile as an effective potential which produces flat galactic rotation curves. If a concrete modified gravity model gives a flat rotation curve, then the parameter Γ that characterizes the lensing effect must take so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…First constraints on the strength of the coupling between an additional modified-gravity scalar, which is responsible for galactic dynamics in the absence of particle dark matter, and photons were derived in Ref. [49] from observations of the lens system SDSS J2141-0001. It was found that the effect of the modified-gravity scalar on the lensing of photons must be of the same order as its effect on the motion of matter within the galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…First constraints on the strength of the coupling between an additional modified-gravity scalar, which is responsible for galactic dynamics in the absence of particle dark matter, and photons were derived in Ref. [49] from observations of the lens system SDSS J2141-0001. It was found that the effect of the modified-gravity scalar on the lensing of photons must be of the same order as its effect on the motion of matter within the galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [122] provides first constraints on the strength of the coupling between photons and an additional scalar field from modified gravity theories, which is responsible for galactic dynamics in the absence of particle DM.…”
Section: Lensing With Symmetron Fieldsmentioning
confidence: 99%